2003
DOI: 10.1590/s0004-282x2003000500016
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia para epilepsia na infância: avaliação neuropsicológica e de qualidade de vida

Abstract: RESUMO -Objetivo: Avaliar e descrever os efeitos advindos da cirurgia para epilepsia quanto aos aspectos neuropsicológicos e de qualidade de vida e relacionar os resultados ao quadro clínico do paciente. Método: Foram avaliadas nove crianças com epilepsia refratária antes e seis meses após a cirurgia através de uma ampla bateria de instrumentos neuropsicológicos e questionário de qualidade de vida. As etiologias e os procedimentos cirúrgicos foram variados. Resultados: Mudanças significativas no QI, no geral, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
1
5
0
6
Order By: Relevance
“…With respect to the overall outcome of QOL, the survey found that almost all patients showed significant improvement, which concurs with other results 3,14,[16][17][18][22][23][24][25][26][27] . Despite the excellent control of seizures, only one of our patients had a decrease in the overall QOL score (subject 13), mainly due to social, school and behavioral factors.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…With respect to the overall outcome of QOL, the survey found that almost all patients showed significant improvement, which concurs with other results 3,14,[16][17][18][22][23][24][25][26][27] . Despite the excellent control of seizures, only one of our patients had a decrease in the overall QOL score (subject 13), mainly due to social, school and behavioral factors.…”
Section: Discussionsupporting
confidence: 88%
“…All subjects indicated a high level of perception of seizure control (attributed to a maximum value when questioned about it). Other studies have also found a high degree of seizure control 14,16,19,26 and positive correlations between the control and the degree of patient satisfaction 14,16,17,[23][24][25][26][27][28] . However, our findings were higher than those of the literature and, again, this is probably due to the strict inclusion criteria in our study and the fact that we have focused on surgery for TLE only, excluding other more serious etiologies.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations